2012
DOI: 10.1007/s11033-012-2299-z
|View full text |Cite
|
Sign up to set email alerts
|

Review: role of carbon sources for in vitro plant growth and development

Abstract: In vitro plant cells, tissues and organ cultures are not fully autotrophic establishing a need for carbohydrates in culture media to maintain the osmotic potential, as well as to serve as energy and carbon sources for developmental processes including shoot proliferation, root induction as well as emission, embryogenesis and organogenesis, which are highly energy demanding developmental processes in plant biology. A variety of carbon sources (both reducing and non-reducing) are used in culture media depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 124 publications
5
87
0
8
Order By: Relevance
“…Sugars are necessary for the function of several parts of morphogenesis, such as the osmolarity balance of the culture medium, skeletal function for the building of various important factors, heterotrotophy/mixotrophy, and regulation of genes responsible for plant growth (Yaseen et al, 2013). Some studies on plants from the Zingiberaceae family have shown that higher sucrose concentrations of 60 to 70 g/L are more efficient for in vitro plant morphogenesis when compared to the usual concentration of 30 g/L.…”
Section: Effect Of Activated Charcoal and Sucrosementioning
confidence: 99%
See 1 more Smart Citation
“…Sugars are necessary for the function of several parts of morphogenesis, such as the osmolarity balance of the culture medium, skeletal function for the building of various important factors, heterotrotophy/mixotrophy, and regulation of genes responsible for plant growth (Yaseen et al, 2013). Some studies on plants from the Zingiberaceae family have shown that higher sucrose concentrations of 60 to 70 g/L are more efficient for in vitro plant morphogenesis when compared to the usual concentration of 30 g/L.…”
Section: Effect Of Activated Charcoal and Sucrosementioning
confidence: 99%
“…Beyond sucrose, other carbon sources have been used in the micropropagation, as is the case of sorbitol, mannitol, fructose, galactose (pentoses) and maltose (disaccharide) (Yaseen et al, 2013). Being the first two, more are used in essays involving minimal cultivation or in germplasm collection establishment (Martins et al, 2011).…”
Section: Effect Of Activated Charcoal and Sucrosementioning
confidence: 99%
“…Moreover, the role of LEAFY COTYLEDON1 (LEC1) gene, that controls embryogenic competence, requires both the auxin and sucrose to promote cell division and embryonic differentiation (Casson and Lindsey 2006). Various exogenous sugars have been used to enhance SE efficiency, indicating that carbon sources play an important role in this process (Yaseen et al 2013). Despite the importance of sucrose metabolism in maintaining the balance between hexose signals and metabolic paths (Koch 2004), there is only one example of the relationship between the content of phytohormones and endogenous sugars during the SE induction currently displayed .…”
Section: Introductionmentioning
confidence: 99%
“…No cultivo in vitro de plantas a fotossíntese é mínima, pois a plântula em desenvolvimento tem suas necessidades de carbono supridas pela adição de sacarose no meio de cultura (YASEEN et al, 2013;GAGO et al, 2014). Já o fototropismo, também não é tão relevante nas condições in vitro, no entanto, em relação à fotomorfogênese a luz tem papel direto nas respostas morfofisiológicas do vegetal, portanto, interessa a elucidação de sua influência sobre as plântulas em crescimento (GEORGE et al, 2008).…”
Section: Introductionunclassified